2012
DOI: 10.1126/science.1218948
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Electrical Transport Across Grain Boundaries in Polycrystalline Graphene

Abstract: Graphene produced by chemical vapor deposition (CVD) is polycrystalline, and scattering of charge carriers at grain boundaries (GBs) could degrade its performance relative to exfoliated, single-crystal graphene. However, the electrical properties of GBs have so far been addressed indirectly without simultaneous knowledge of their locations and structures. We present electrical measurements on individual GBs in CVD graphene first imaged by transmission electron microscopy. Unexpectedly, the electrical conductan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
623
3
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(658 citation statements)
references
References 29 publications
29
623
3
3
Order By: Relevance
“…The gate voltage dependence of this result is consistent with report from Tsen et al 37 if we assume that …”
Section: Grain Boundaries In Cvd Graphenesupporting
confidence: 93%
“…The gate voltage dependence of this result is consistent with report from Tsen et al 37 if we assume that …”
Section: Grain Boundaries In Cvd Graphenesupporting
confidence: 93%
“…Larger sheets of few-layer or monolayer graphene can now be directly synthesized via chemical vapor deposition (CVD) on nickel or copper substrates [54,55] with mobilities rivalling the ones of exfoliated samples. [56] For samples placed on SiO 2 /Si wafers, mobilities on the order of ~1,000-10,000 cm 2 /Vs are now routinely observed and regarded as the standard for graphene transistor products for biochemical sensing applications. [57] The electronic performances of CVD graphene [58] can be significantly enhanced by growing single-crystal graphene free of grain boundaries [59] and by using a BN substrate similarly to exfoliated graphene, with which mobility up to ~50,000-350,000 cm 2 /Vs can be achieved.…”
Section: Sensing With Graphene Of High Carrier Mobilitymentioning
confidence: 99%
“…In addition, GBs with larger grain size exhibit relatively better conductive performance [247,251]. On the other hand, a few experiments [209,252,253] observed that the configuration of GBs or the variation of grain sizes had little effects on the conductive properties of graphene. Recent study [254] also suggested that increasing grain size would be an inefficient way to improve the electrical conductivity of graphene when the grain size is larger than 1 μm.…”
Section: Disorders In Graphene Structurementioning
confidence: 99%